Análisis de los factores que afectan la variabilidad del precio del barril de petroleo en el Ecuador y su impacto en la economía durante el periodo 2009-2014 - Solórzano Cedeño Sandra Dolores (2015)
The need for this analysis is to find answers to the question that individuals are made every day on the incidence of the change in price of a barrel of oil in the economy. In the analysis methods were used: analytical, hypothetical or deductive and scientific, which are necessary for gathering information and conducting the corresponding analysis, in order to know the effect that causes the change in price of a barrel of oil Ecuador's economy; types of research used in this analysis are: applied research that allows a practical analysis, analytical to help us look for causes and effects, hindsight and foresight will allow us to examine the causes and effects in the present and future, and Finally the retrolective as information from secondary sources will be used. The results of this study show the impact of oil price changes in the economy; This analysis requires information relevant study period, year 2009 - 2014, based on data obtained from sources within the fair industry of our country, such as: Ministry of Finance, Central Bank of Ecuador, Ministry of Policy Coordination economic, Secretary of Hydrocarbons of Ecuador, among others. The investigation revealed that the price of a barrel of oil in the international market,has always been the indicator which have sustained, its provisions economic, supply and demand is one of the main factors influencing change price per barrel